Gaseous emissions and particle size distribution of dual-mode dual-fuel diesel-gasoline concept from low to full load. (25th June 2017) - Benajes, Jesús; García, Antonio; Monsalve-Serrano, Javier; Boronat, Vicente
Highlights: Dual-mode dual-fuel arises as an evolution of low temperature combustion strategies. No relation is observed between smoke and particle matter at dual-mode dual-fuel. Higher number of particles obtained for dual-mode dual-fuel than conventional diesel. Nucleation moves to accumulation mode as engine load increases at dual-mode dual-fuel. Mainly diffusive strategy shows clear relation between smoke and particle matter. Abstract: Low temperature combustion concepts are in focus of study nowadays as a method to avoid the NOx-soot trade-off existing with conventional diesel combustion. One of the most promising strategy is known as reactivity controlled compression ignition because of its high thermal efficiency and the ultra-low nitrogen oxides and soot emissions. However, this concept presents several challenges such as the high levels of carbon monoxide and unburned hydrocarbons promoted at low load and unacceptable levels of pressure rise rate at high load. Therefore, to mitigate these shortcomings the dual-mode dual-fuel concept, combining reactivity controlled compression ignition and diffusive dual-fuel diesel-gasoline combustion, has been developed. Total number of particles is also limited by the emission standards. Previous studies focused in particles emissions carried out by the research community present particle size distribution, composition and mass of the particles on reactivity controlled compression ignition combustion mode. Additional studies were carried out in order to identify the components of these particles, being partially formed of volatiles, and reflects that particles are smaller than at conventional diesel combustion, presenting higher number of particles from nucleation mode than from accumulation mode. Dual-Mode Dual-Fuel concept may present a different behavior for particle distribution with respect to the conventional diesel combustion or the traditional low temperature concepts due to the nature of the particles. The objective of the present study is to measure the particle size distribution as well as gaseous emissions of this new Dual-Mode Dual-Fuel concept from low load to full load for a representative engine speed of 1200 rpm. Main results of this study suggest that Dual-Mode Dual-Fuel concept promotes higher quantity of particles than conventional diesel combustion despite of providing less smoke. In addition, nucleation mode particles dominate the particle size distribution for the new combustion concept at low load and moves towards accumulation mode domination at full load.